Human Resource Management Transformation in the Era of Disruption: Integrating Strategic Efficiency with a Human Touch for Sustainable Organizational Excellence - Zuhdi Esha; Dewi Cahyani; Moh. Ali (al-Afkar, Journal For Islamic Studies, 2026)
The worldwide workplace has undergone fundamental change due to technological disruptions, a shift in social norms caused by pandemics, and corporate disruption. In this context, Manajemen Sumber Daya Manusia (MSDM) continues to function as a specialized administrative unit and has developed into a crucial strategic tool for the organization's operations. The purpose of this article is to examine the conceptual evolution of MSDM from a mechanistic approach to a more holistic and humanistic perspective. Through a review of recent literature and conceptual analysis, this article explains how the functions of MSDM—rekrutmen, pengembangan, kinerja management, compensation, and industrial connection—are adapted to contemporary challenges like artificial intelligence (AI), hibrid work models, gig economy, and mental health.. This article argues that the effective age of MSDM is based on the synergy between the development of technology for data-driven efficiency and the development of humanist philosophy that promotes employee martabat, kesejahteraan, and kebermaknaan kerja as the foundation of each policy. By integrating these two elements, an organization can not only achieve productivity and innovation but also create a tangguh, inclusive, and sustainable work environment. This article concludes with practical recommendations for MSDM practitioners and organizational leaders to develop strategies that prioritize kemanusiaan above strategic goals.